Coronavirus disease 2019 induces multi‐lineage, morphologic changes in peripheral blood cells. Issue 1 (29th June 2020) - Lüke, Florian; Orsó, Evelyn; Kirsten, Jana; Poeck, Hendrik; Grube, Matthias; Wolff, Daniel; Burkhardt, Ralph; Lunz, Dirk; Lubnow, Matthias; Schmidt, Barbara; Hitzenbichler, Florian; Hanses, Frank; et al.
Abstract: The clinical course of coronavirus disease 2019 (COVID‐19) varies from mild symptoms to acute respiratory distress syndrome, hyperinflammation, and coagulation disorder. The hematopoietic system plays a critical role in the observed hyperinflammation, particularly in severely ill patients. We conducted a prospective diagnostic study performing a blood differential analyzing morphologic changes in peripheral blood of COVID‐19 patients. COVID‐19 associated morphologic changes were defined in a training cohort and subsequently validated in a second cohort (n = 45). Morphologic aberrations were further analyzed by electron microscopy (EM) and flow cytometry of lymphocytes was performed. We included 45 COVID‐19 patients in our study (median age 58 years; 82% on intensive care unit). The blood differential showed a specific pattern of pronounced multi‐lineage aberrations in lymphocytes (80%) and monocytes (91%) of patients. Overall, 84%, 98%, and 98% exhibited aberrations in granulopoiesis, erythropoiesis, and thrombopoiesis, respectively. Electron microscopy revealed the ultrastructural equivalents of the observed changes and confirmed the multi‐lineage aberrations already seen by light microscopy. The morphologic pattern caused by COVID‐19 is characteristic and underlines the serious perturbation of the hematopoietic system. We defined a hematologic COVID‐19 pattern to facilitate further independent diagnostic analysis and to investigate the impact on the hematologic system during the clinical course of COVID‐19 patients.